Potential for Timberline Advance in Northern Finland, as Revealed by Monitoring during 1983-99 - Juntunen, V.; Neuvonen, S.; Norokorpi, Y.; Tasanen, T. (ARCTIC, 2002)
Seedling density, tree density and basal area of Scots pine (Pinus sylvestris L.) and Norway spruce (Picea abies (L.) Karst) were monitored and compared in the timberline areas of northern Finland during the period 1983-99. Rows of 9-12 circular plots were established at 13 localities in four regions: pine-dominated northern and southern regions and spruce-dominated western and eastern regions. Temporal changes were monitored in three altitudinal zones: in the forest, at the coniferous timberline (where forest canopy closure ceases), and at the tree line (where coniferous trees higher than 2 m cease). Pine seedling densities decreased abruptly in the southern region, especially at the timberline, but increased slightly in the northern region. The zone "region" change interaction was significant. The change in spruce seedling densities was small in the forest and timberline zones, but the densities more than doubled at the tree line. Tree density and basal area increased in all the zones and regions. New regeneration and tree establishment during the study period indicate a potential for the tree line to advance. However, there was great heterogeneity in regeneration and seedling establishment among the localities. La densité des semis, la densité des arbres et la surface terrière du pin sylvestre (Pinus sylvestris L.) et de l'épinette de Norvège (Picea abies [L.] Karst) ont fait l'objet d'une étude et d'une comparaison dans des zones situées à la limite de la forêt de la Finlande septentrionale durant la période allant de 1983 à 1999. Des rangées de 9 à 12 parcelles circulaires ont été créées à 13 sites répartis dans 4 zones: les régions septentrionale et méridionale où dominait le pin sylvestre, et les régions occidentale et orientale où dominait l'épinette de Norvège. On a mesuré les changements temporels dans 3 zones d'altitude différente: dans la forêt, à la limite de la forêt de conifères (là où cesse la fermeture du couvert forestier), et à la limite des arbres (là où cessent les conifères de plus de 2 m ...